Nurse’s Spiritual Care Competencies to Patient with End Stage Breast Cancer - Nurul Rezki Anisa; Kadek Ayu Erika; Rini Rachmawaty (International Journal of Public Health Science (IJPHS), 2018)
Cancer has many side effects on patient’s physic and mostly on mental which may affect on their quality of life. Physically most patients feel fatigue, insomnia, anorexia, nausea, and vomit while mentally they feel emotional disturbances such as anxiety, stress, or depression. One of the methods to that appropriate to overcome both of the conditions is spiritual care. Many research found that because spiritual care associated with better wellbeing, less emotional disturbance, less substance abuse, greater social support, better health behaviours, so it has impact to longer survival periods. This research aimed to investigate nurse’s spiritual care competencies to patients with end stage cancer. This was descriptive study design employed Spiritual Care Competencies Scale (SCCS) instrument. A total sampling of 24 nurses working in Oncology department in Dr. Wahidin Sudirohusodo Hospital were recruited. This research found that there are 12 nurses (50 %) that work in oncology department have low competencies of spiritual care. Involving spiritual care is associated with better wellbeing and longer survival periods. Therefore, it is necessary to increase the competence of nurses on spiritual care in meeting the spiritual needs of patients with end stage breast cancer. A training of spiritual care can be an alternative for nurses to improve spiritual care in hospitals.